Review of the digger wasps of the genus Chilosphex Menke in Bohart and Menke, 1976 (Hymenoptera: Sphecidae: Prionychini) - Danilov, Yuriy N.; Odintsev, Oleg A. (Zootaxa, 2022)
All available data about the digger wasp genus Chilosphex Menke in Bohart and Menke, 1976 is summarized. The melanistic form of Ch. argyrius (Brullé, 1833) from North Caucasus (Dagestan) is recorded and illustrated. Chilosphex pseudargyrius (Roth in de Beaumont, 1967) is newly recorded from Iran and Ch. argyrius from Bulgaria. A key to both species is provided.